Gastrointestinal Carriage of Vancomycin-Resistant Enterococci and Carbapenem-Resistant Gram-Negative Bacteria in an Endemic Setting: Prevalence, Risk Factors, and Outcomes - Vasilakopoulou, Alexandra; Karakosta, Polyxeni; Vourli, Sophia; Tarpatzi, Aikaterini; Varda, Paraskevi; Kostoula, Maria; Antoniadou, Anastasia; Pournaras, Spyros (Frontiers in Public Health, 2020)
Background: Gastrointestinal carriage of vancomycin-resistant enterococci (VRE) and carbapenem-resistant Gram-negative bacteria (CRGN) constitutes a major public health concern as it may be followed by clinical infection development or lead to intra-hospital dissemination. Detection of carriers and implementation of infection control measures are essential in every hospital. In this study we determined the point prevalence of VRE and CRGN in the fecal flora of the inpatients of a tertiary university hospital in Greece. We determined risk factors for carriage and examined the impact of carriage on hospital outcomes. Materials/methods: A point prevalence study of VRE/CRGN rectal carriage of inpatients was conducted on March 2018. Specimens were selectively cultured for VRE/CRGN, microorganisms were biochemically identified, submitted to antibiotic susceptibility testing and tested for carbapenemase production. Data on potential risk factors and hospital outcomes were collected at the time of culture and until hospital discharge. Multivariable logistic and linear regression models were used adjusting for confounders. Results: 491 patients were enrolled in the study. Of them, 64 (13.0%) were positive for VRE carriage, 40 (8.2%) for CRGN and 10 patients (2.1%) for both VRE and CRGN. VRE carriage was independently associated with age over 65 years (adjusted OR: 2.4 [95%CI: 1.3, 4.5]) and length of stay (LOS) before rectal sampling (OR: 1.1 [95%CI: 1.0, 1.1]). Carriage of CRGN was associated with 11 days increase of LOS after rectal sampling (β-coef: 11.4 [95%CI: 1.6, 21.2]), with 3.5-fold increased risk of acquiring a resistant pathogen after rectal swabbing (RR: 3.5 [95%CI 1.2, 9.9]) and with 6-fold increased risk of mortality (RR: 6.1 [95%CI: 2.1, 17.9]), after adjusting for sex, age and comorbidity index. Conclusions: High prevalence rates were found for VRE and CRGN carriage among the inpatients of our hospital. Prolonged hospitalization and age were independent risk factors for VRE carriage, while CRGN carriage was associated with increased risk of acquiring a resistant pathogen, prolonged hospital stay and increased mortality.